Determination of optimal in vitro conditions for camel alternative complement pathway assay - CHOPRA, V; KASHYAP, S K (The Indian Journal of Animal Sciences, 2014)
Optimal in vitro testing conditions for camel,alternative complement pathway assay were determined. Effect of following variables were tested: heterologous erythrocytes, pH, ionic strength and Mg2+ ion concentration of diluent, incubation time and temperature. The standard system of titrating the He levels consisted of rabbit erythrocytes as target cells, veronal buffer saline with EGTA, pH 7.3, ionic strength 0.10 M, Mg2+ concentration 4mM at 37Â°C temperature for 60 min incubation.